Managerial Perceptions Concerning Nondisclosure of Sustainability Issues: A Case of Two Selected Banks in Bangladesh - Sobhani, Farid A.; Amran, Azlan (Asian Business Review, 2012)
This paper aims to explore the perceptions of senior bankers concerning nondisclosure of sustainability issues within the context of Bangladesh. The main objective of this paper is to critically examine the reasons for managerial reluctance to report corporate sustainability issues for two competing banks in Bangladesh, in general, and crucial issues, such as energy, human rights, and environmental issues, in particular. The study considered the perceptions of senior managers of two selected banks as gathered through an interview process. In total, 20 senior bankers of the two banks were interviewed to ascertain their perceptions concerning nondisclosure of corporate sustainability issues. The study found numerous reasons behind the nondisclosure of sustainability issues, such as the lack of sufficient resources, absence of the practice by other banks, lack of a legal framework, lack of pressure from any other concern, absence of a sustainable corporate plan, shortage of manpower, lack of infrastructure and logistic support, and the cost involved. From an institutional perspective, organizational changes are not always favourable, sometimes organizational actors adapt strategies to resist any change. This research provides an explanation for non-disclosed items in the two selected banks’ sustainability reporting. The findings provide some indication of how such practices can be developed further.
Keywords: Sustainability issue; Nondisclosure; Banks; Institutional theory; Bangladesh